Strategi Inovatif untuk Meningkatkan Kesadaran dan Kepatuhan Terhadap Kesehatan dan Keselamatan Kerja di Industri Manufaktur - Bahsin, Alkaf Munis; Abdul Rohim Tualeka (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This study aims to explore innovative strategies that can increase awareness and compliance with occupational health and safety in the manufacturing industry. The research method used is a quantitative approach using a questionnaire to collect data from 250 respondents who are workers in various manufacturing factories. Data analysis was performed through descriptive and inferential statistical techniques. The main findings of this study indicate that the implementation of innovative strategies involving awareness campaigns, specialized training, and the use of advanced technology can significantly increase workers' awareness and compliance with occupational health and safety. In this case, workers' awareness regarding risks and hazards in the workplace has increased significantly, while the level of adherence to safety procedures and the use of personal protective equipment has also increased significantly The practical implications of these findings are that innovative strategies can be effective means of increasing awareness and compliance with occupational health and safety in the manufacturing industry. Companies may consider implementing focused awareness campaigns, providing regular specialized training, and leveraging advanced technologies such as sensors and automation systems to strengthen a safety culture in the workplace. This research makes an important contribution to the understanding of efforts to improve occupational health and safety in the manufacturing industry. The results of this study can be used as a basis for designing programs and policies that are more effective in managing risks and improving work safety in manufacturing environments